The Effect Of Work Environment, Competence, And Internal Communication On The Work Productivity Of Employees At Regional Secretariat Of Seluma Regency - Jingga Febbya Cahyani; Ida Anggriani; Tri Febrina Melinda (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2026)
A conducive working environment, both physically and psychologically, can increase employee motivation and comfort at work. Employee competence, which includes knowledge, skills, and professional attitudes, is key to completing tasks efficiently. Meanwhile, smooth and effective internal communication between employees and superiors supports the smooth flow of information and teamwork. Therefore, this study aims to examine how these three factors affect the work productivity of employees at Regional Secretariat of Seluma Regency. The purpose of this study is to determine whether the work environment, competence, and internal communication simultaneously affect the work productivity of employees at Regional Secretariat of Seluma Regency. This study is a quantitative descriptive study. The data collection method in this study used a questionnaire technique, with a sample of 107 respondents. The results showed that the multiple linear regression was Y 21.170 + 0.143 X1 + 0.316 X2 + + 0.144 X3 + 3.820. Where the coefficient has a positive value, it means that there is a positive or unidirectional relationship between the variables of Work Environment (X1), Competence (X2) and Internal Communication (X3) with a value of 0 (zero), then the Work Productivity of Employees at Regional Secretariat of Seluma Regency. The results of the Work Environment (XI) test show that t count 2.462 > t table 1.659 and significance 0.015 < 0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning that the Work Environment (XI) has a positive and significant effect on the Work Productivity of Employees. The Competence (X2) test results show that t count 5.333 > t table 1.659 and significance 0.000 < 0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning that Competence (X2) has a positive and significant effect on the Work Productivity of Employees. The results of the Internal Communication test (X3) show that t count 2.532 > t table 1.659 and significance 0.015 < 0.05, so the results of the Ha hypothesis are accepted and Ho is rejected, meaning that Internal Communication (X3) has a positive and significant effect on the Work Productivity of Employees at Regional Secretariat of Seluma Regency. Based on a comparison of F count with F table, the value F count is greater than F table, namely 15.549 > 2.46. Therefore, it can be concluded that the hypothesis is accepted, meaning that there is a simultaneous influence between the Work Environment (XI), Competence (X2), and Internal Communication (X3) on the Work Productivity (Y) of Employees at Regional Secretariat of Seluma Regency. This can be seen at a significance level of 0.000 < 0.05.